1976
DOI: 10.1042/bj1600745
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological degradation of bile acids. Nitrogenous hexahydroindane derivatives formed from cholic acid by Streptomyces rubescens

Abstract: The metabolism of cholic acid (I) by Streptomyces rubescens was investigated. This organism effected ring A cleavage, side-chain shortening and amide bond formation and gave the following metabolites: (4R)-4-[4alpha-(2-carboxyethyl)-3aalpha-hexahydro-7abeta-methyl-5-oxoindan-1 beta-yl]valeric acid (IIa) and its mono-amide (valeramide) (IIb); and 2,3,4,6, 6abeta,7,8,9,9aalpha,9bbeta-decahydro-6abeta-methyl-1H-cyclopenta[f]quinoline-3,7-dione(IIIe)and its homologues with the beta-oriented side chains, valeric ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 10 publications
4
19
0
Order By: Relevance
“…This, and the NMR data in particular, indicated that the compound could be the 6-lactam compound (14B) [NMR,6 7.47 (1 H, broad s, disappears after D 2 0 exchange, NH), 4.77 (1 H, d of d, J2,2 Hz, C(6)H), 4.49 (1 H d of d, J2,2 Hz, C(7a)H), 1.02 (s, 7aPCH3). This structural derivation is supported by comparison with the spectral data published for the &lactam (14A) by Hayakawa et al (1976). In particular, compound (14A) is reported to have a Amax.…”
Section: Isolation Of the Intermediates Formed By M U I7 From Deoxysupporting
confidence: 62%
“…This, and the NMR data in particular, indicated that the compound could be the 6-lactam compound (14B) [NMR,6 7.47 (1 H, broad s, disappears after D 2 0 exchange, NH), 4.77 (1 H, d of d, J2,2 Hz, C(6)H), 4.49 (1 H d of d, J2,2 Hz, C(7a)H), 1.02 (s, 7aPCH3). This structural derivation is supported by comparison with the spectral data published for the &lactam (14A) by Hayakawa et al (1976). In particular, compound (14A) is reported to have a Amax.…”
Section: Isolation Of the Intermediates Formed By M U I7 From Deoxysupporting
confidence: 62%
“…This suggests that the degradation of these bile acids with this organism also follows this 9,lO-seco-phenol pathway containing the 6a-, 701-or 12a-dehydroxylation discussed above and produces 46. S. rubescens converted cholic acid ( 1 ) into 46 and several enaminolactam derivatives, which were described as a general formula 50 in Scheme 6 and postulated to be formed from the corresponding 8-oxocarboxylic acids 37, 46 and 51, in addition to 5, 6, 7 and 8 in Scheme 1 (HAYAKAWA et al 1976b foniicd ti) t h i b organi 11. L must iiiention here the soinen hat peculiar biodegradability of iiiicroorganisnis 1% I ch can 1itiii.w cholic acid as a carbon source.…”
Section: Formation and Degradation Of Perhydroindane Derivativesmentioning
confidence: 99%
“…Secosteroids with novel molecular structures have also been obtained after the ring cleavage [14], [15]. Thus, microbial cleavage of steroid rings A-D has been reported to give unusual products that could not be synthesized by conventional chemical syntheses [16]. A sequential ring opening and modification of the steroid nucleus resulting in innovative products has been proposed by Hayakawa [17].…”
Section: Introductionmentioning
confidence: 97%